2022
DOI: 10.1177/09567976221091211
|View full text |Cite
|
Sign up to set email alerts
|

Following Other People’s Footsteps: A Contextual-Attraction Effect Induced by Biological Motion

Abstract: Our visual system is bombarded with numerous social interactions that form intangible social bonds among people, as exemplified by synchronized walking in crowds. Here, we investigated whether these perceived social bonds implicitly intrude on visual perception and induce a contextual effect. Using multiple point-light walkers and a classical contextual paradigm, we tested 72 college-age adults across six experiments and found that the perceived direction of the central walker was attracted toward the directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 46 publications
(58 reference statements)
5
7
1
Order By: Relevance
“…Different from the simultaneous contrast effect of gender observed here, there are some other studies showing an assimilation contextual effect in space (e.g., on emotion in Lecker et al, 2020; Lecker et al, 2017; on walking direction in Cheng et al, 2022). Generally, these effects can be well accounted for by a perceptual bias induced by prior experience rather than lateral inhibition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Different from the simultaneous contrast effect of gender observed here, there are some other studies showing an assimilation contextual effect in space (e.g., on emotion in Lecker et al, 2020; Lecker et al, 2017; on walking direction in Cheng et al, 2022). Generally, these effects can be well accounted for by a perceptual bias induced by prior experience rather than lateral inhibition.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be noted that previous studies investigating the spatial contextual effect of high‐level visual features did not reveal such a contrast effect (Bindemann et al, 2005; Cheng et al, 2022; Lecker et al, 2017, 2020). In a flanker task, Bindemann et al (2005) did not observe a reaction facilitation in judging the gender of a central face when it was congruent than incongruent with the gender of the simultaneously presented surrounding faces, possibly because that face gender judgement was less susceptible to its context if the test faces were with explicit gender information.…”
Section: Discussionmentioning
confidence: 81%
“…These results add onto a burgeoning literature investigating synchrony in social perception (Alp et al, 2017; Cheng et al, 2022; Cracco, Lee, et al, 2022; Tsantani et al, 2022). In a functional MRI study, Tsantani et al (2022) showed that synchrony between the head movements of two agents could be decoded in brain areas of the social perception network, such as the posterior superior temporal cortex and the extrastriate body area.…”
Section: Discussionsupporting
confidence: 67%
“…Recent research has provided initial evidence that synchrony can indeed shape the processing of other people’s actions (Alp et al, 2017; Cheng et al, 2022; Cracco, Lee, et al, 2022; Tsantani et al, 2022) or emotional expressions (Elias et al, 2017). However, in addition to being restricted to synchrony, this research has not yet established whether these effects are specific to biological agents or are more general in nature.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of perceived walking direction, repeated exposure to a specific walking direction (e.g., viewing an animated stimulus walking to the left) produces a repulsive perceptual aftereffect, such that the perceived angle at which subsequently presented stimuli are perceived as walking is biased away from the angle to which the observer was adapted ( Jackson & Blake, 2010 ; Chen, Boyce, Palmer, & Clifford, 2023 ). In contrast, Cheng, Liu, Yuan, and Jiang (2022) recently found an attractive effect of spatial context on perceived walking direction, such that the perceived direction of a walker was biased toward the walking direction of a set of surrounding walkers. Although no single study has yet compared spatial and temporal effects on the perception of walking direction, these previous studies raise a question of why these effects seem to differ in being attractive and repulsive, respectively.…”
Section: Introductionmentioning
confidence: 92%